Identifikasi Jenis Liana Dan Tumbuhan Penopangnya Di Blok Perlindungan Taman Hutan Raya Wan Abdul Rachman - Tiopan Tua Halomoan Simamora; Indriyanto Indriyanto; Afif Bintoro (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Liana is one type of plant that becomes typical characteristic of a tropical rain forest ecosystem and its presence adds to the diversity of plant species in the forest ecosystem. The purposes of the study were to identify the species of liana, species of cantilever plant, and to know the number of liana species associated with the species of cantilever plant in the protection block of Wan Abdul Rachman Great Forest Park, especially in the area of Way Balau Sub watershed. The research was conducted on September to Oktober 2013. The sampling method was used line terraced layer. The size of each sample plot was 20 m x 20 m with sub plots 10 m x 10 m, 5 m x 5 m, 2 m x 2 m. Liana and cantilever plants species were inventoried by 0.2% sampling intensity from 796.50 ha. Observed variables were the species and the number of lianas, spesies of cantilever plant and its number. The result of research were identified 8 species of liana and 35 spesies of cantilever plants. Liana density was 1,599 individual/ha and cantilever plant density was 1,594 individual/ha, and it had a good enough distribution because there was no dominant species. The plant that most liked by liana is dadap (Erythrina lithosperma) and liana that mostly found is rayutan (Paederia tomentosa). Keywords: cantilever plant, liana, Protection Block of Wan Abdul Rachman GreatForest Park